2019
DOI: 10.1051/matecconf/201925801010
|View full text |Cite
|
Sign up to set email alerts
|

A mockup unit of the an-eco budget bamboo chalet: design and cost estimation analysis

Abstract: To succeed by 2050, Malaysia visions would need to be ecologically sustainable. To align with this strategy, a mock-up unit of an-eco budget bamboo chalet is proposed and designed with the aim to provide an affordable and sustainable chalet using local sustainability features and expand the use of natural resources. A sustainable bamboo chalet requires proper initial treatments and preservation in maintaining its esthetic appearance and strength. Otherwise, it can be less durable and under certain circumstance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Bamboo is a type of grass that grows rapidly and can be harvested within three to five years, making it a highly sustainable and renewable resource for construction. In addition, bamboo has a higher strength-to-weight ratio than traditional building materials such as wood and concrete, making it an ideal material for building lightweight structures [51]. Bamboo has been used in various construction projects in Malaysia, such as the Bamboo Playhouse in Kuala Lumpur, which was built using bamboo as the primary construction material.…”
Section: Bamboomentioning
confidence: 99%
See 1 more Smart Citation
“…Bamboo is a type of grass that grows rapidly and can be harvested within three to five years, making it a highly sustainable and renewable resource for construction. In addition, bamboo has a higher strength-to-weight ratio than traditional building materials such as wood and concrete, making it an ideal material for building lightweight structures [51]. Bamboo has been used in various construction projects in Malaysia, such as the Bamboo Playhouse in Kuala Lumpur, which was built using bamboo as the primary construction material.…”
Section: Bamboomentioning
confidence: 99%
“…Bamboo has also been used in the construction of low-cost housing projects, such as the Rumah Aspirasi Rakyat (RAR) in Sabah, which used bamboo as a substitute for traditional building materials [52]. A previous study compared the estimated construction cost, projected maintenance cost, and overall life cycle cost of an eco-budget chalet built with two types of Malaysian bamboo (Dendrocalamus asper and Bambusa vulgaris) as the main construction material with the same chalet design built with reinforced concrete as the main construction material [51,53]. Despite the advantages of bamboo as a green material, there are also some potential drawbacks to consider.…”
Section: Bamboomentioning
confidence: 99%
“…Bamboo is a natural fiber composite used for household application, furniture, and food (Azmy et al 1991;Yap et al 2017). This natural fiber could substitute the synthetic fiber reinforced plastic because it is more durable, economical, and sustainable for green building (Mansor et al 2019). An et al (2020) found out that the mechanical strength of material bamboo (bamboo fiber) is an excellent fit for paper products.…”
Section: Introductionmentioning
confidence: 99%